Vitamin D3 reduces the viability of cancer cells in vitro and retard the EAC tumors growth in mice - Vidya G. Bettada; Chaithanya G. Basavaraju; Shalini H. Doreswamy; SubbaRao V. Tulimilli; Rimshia Naaz; Siva Dallavalasa; Paramahans V. Salimath; Anjali Devi S. Bettadapura; Asha Srinivasan; Rajalakshmi Ramashetty; Suma M. Natraj; SubbaRao V. Madhunapantula (PLoS ONE, 2025)
Prior studies from our laboratory have shown that cancer cells exposed to vitamin D3 exhibited reduced proliferation in breast cancer cells due to the upregulation of p53 and downregulation of cyclin-D1. Furthermore, in mice, our group has demonstrated that administration of 125 µg/kg of vitamin D3 retarded the growth of EAC tumors. But, it is unknown whether vitamin D3 exerts similar anti-cancer effects against cell lines representing carcinomas of the liver, colon and rectum, cervix, and brain. It is also unknown whether administration of vitamin D3 by i.p alone is sufficient for better tumor inhibition or combined administration consisting of i.p. and intratumoral (i.t.) routes is required. Furthermore, the ability of vitamin D3 in reducing the tumor growth in normal and diabetic mice has not been studied to date. Addressing these lacunae, we have prepared the dose and time response curves for vitamin D3 against different cancer cells and assessed the impact on pathways regulating cell survival and cell proliferation. A dose-dependent decrease in the (a) number of proliferating cells; (b) viability and (c) an increase in apoptosis (as evidenced by increased cleaved caspase-3) were observed with vitamin D treatment. Mechanistically, low dose vitamin D3 (15.62µM and 31.25µM) increased the expression of p53 and p21 at 24h and 48h of treatment. Interestingly, we could only observe minor changes in the expression of Bax, Bcl2 and Survivin proteins with vitamin D3 treatment. In mice, i.p. and i.t. combination reduced the tumor growth much more effectively compared to i.p. alone. Our data also showed that vitamin D3 could retard tumors developing in normal and hyperglycaemic mice. In summary, vitamin D3 is a potent anti-cancer agent, hence, is recommend for further development to treat cancers.